BRICS-Plus: the New Force in Global Governance - Ya. D. Lissovolik (Международная аналитика)
The global economy is currently experiencing unprecedented changes as the BRICS nations establish themselves as a signifi cant power center and a crucial factor in the transformation of the international economic framework. Following China’s chairmanship of BRICS, which culminated in the BRICS+ meetings with a diverse range of emerging market economies, these and other countries have expressed their desire to join the BRICS group. The expansion process was largely catalyzed by the openness exhibited by BRICS through the BRICS+ format. The main question at this juncture is how the BRICS+ format will develop and whether it can enhance the position of BRICS in the global arena and among the Global South. This paper explores some of the opportunities presented by the BRICS+ concept in the creation of new global governance, particularly through the establishment of platforms – including those in the real sector and fi nancial platforms aimed at promoting greater cooperation among the sovereign wealth funds and regional development banks of the Global South. Another critical area is the launch of a new reserve currency that could serve as the foundation for greater economic integration across the broad platform of the developing world.